Bloody Sunday and the Rule of Law in Northern Ireland - Walsh, D. author. aut Link
XIV, 349 p.
Keywords: Drawing on original research into explosive evidence which had been concealed for twenty-five years, this book offers a devastating critique of the official Widgery Inquiry into the massacre of innocent and unarmed civilians by British soldiers on Bloody Sunday. It exposes the Inquiry as a gross denial of justice and the rule of law. Expert analysis of the subordination of law to security policy in Northern Ireland reveals that the Bloody Sunday experience is an integral part of a sustained pattern. Belated prospects for a restoration of justice and the rule of law are found in the Good Friday Peace Agreement and the unprecedented establishment of a second Tribunal of Inquiry into Bloody Sunday.